Experiências de acesso e permanência ao Sistema Único de Saúde por lésbicas e mulheres bissexuais - Reis, Dominique da Silva (2023)
In the last 20 years, it was shown a notable advance in the discussions of gender and sexual orientation in the health interface, we can mention the creations of the Brazil Without Homophobia Program, the National Policy for Integral Attention to Women's Health, and the National Policy for Integral Health for Lesbians, Gays, Bisexuals, Transvestites and Transsexuals as important documents. Despite this, it’s been observed a failure to implement these policies. The low adherence of lesbians and bisexual women to health services may be due to discrimination, consultations based on the heteronormative model and the lack of professional training for quality care for their specificities. These practices deny the right to health and violate the principles of equity and universality established by the Unified Health System. In this direction, it’s proposed to analyze the experiences of access and permanence of lesbians and bisexual women to the health services of the Unified Health System, in the city of Cuiabá-MT. For this, we initially carried out an Integrative Review of scientific publications about access and/or permanence in Brazilian health services by lesbian and bisexual women produced between 2011 and 2021. Subsequently, qualitative research was carried out with a cartographic approach through 14 interviews with lesbians and bisexual women who use the health services of the Unified Health System in the city of Cuiabá-MT. For the analysis of the narratives, the assumptions of Thematic Content Analysis were used. As a result of the first stage of the research, the following challenges were highlighted in the access and permanence of lesbians and bisexual women: misconceptions of affective and sexual practices, which were subdivided into: pathologization of homosexuality and bisexuality; Discrimination and the issue of STIs; and the absence of professional qualification, which was subdivided into: absence of acceptance. In the second stage of the research, through the analysis of the interviews, it was possible to analyze the experiences of access and permanence of lesbians and bisexual women in the municipality of Cuiabá, and through their perceptions about the health services, it was possible to identify great proximity to the challenges faced punctuated in the literature already produced. With this, it is concluded that the processes of exclusion, erasure, and invisibility of these lives aggravate processes of illness and cause their extermination.